Manegement of National Commitment through Strengthening Religious Moderation in Academics at Islamic Religious Universities - Muhammad Fazis; Syaiful Marwan (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to provide descriptive information regarding the dynamics of concepts and management that are understood by academics of Islamic Religious Higher Education campuses with their roles as citizens. As citizens, academics get a strengthening of national commitment from Pancasila and Citizenship Education courses at the beginning of the semester as character building on campus through the concept of religious moderation. The method used is descriptive qualitative with a case study design. The results obtained are data obtained according to indicators of understanding of religious moderation. Respondents were considered to have had an attitude of religious moderation related to national commitment and managed an attitude of commitment as part of the Indonesian nation. However, it needs to be maximized by individuals as academic beings in placing themselves and adapting to the environment.